Integrasi Koperasi Dan Bumdes Sebagai Lembaga Usaha Desa Dalam Perspektif Hukum Terhadap Problematika Dan Peluang Regulasi - Santo, Maria Fransiska Owa da (Riviera Publishing, 2025)
Cooperatives and Village-Owned Enterprises (BUMDes) are two economic institutional entities that have a strategic role in realizing the welfare of village communities. In the midst of the challenges of rural development and the need to strengthen the institutions of people's businesses, the idea of institutional integration between cooperatives and BUMDes emerged as an alternative to an inclusive and sustainable business model. However, the difference in juridical character between the two raises legal problems that have not been explicitly regulated in the national legal system. This study aims to analyze the juridical aspects of the institutional integration of cooperatives and BUMDes, using a normative legal approach through the study of laws and regulations, legal doctrines, and the results of previous research. The results of the study show that despite the opportunity for institutional synergy, structural integration between the two still faces normative constraints, especially related to differences in legal regimes, financial accountability, and asset ownership. Therefore, legal reconstruction is needed through regulatory harmonization, both in the form of functional cooperation based on cooperation agreements, as well as the formulation of new regulations that allow the integration of village business institutions legally and effectively. This study is expected to contribute to the development of a legal system that supports community-based village economic transformation.